Biometric and condition index of Anadara antiquata (Bivalvia: Arcidae) from the intertidal area of Lhokseumawe, Indonesia - Kafi, Siti Umayyah; Zulfikar, Zulfikar; Khalil, Munawar (Universitas Malikussaleh, 2024)
Although the biometric characteristics and condition indices of bivalves, including Anadara antiquata, are well-studied, their relationship with environmental factors in tropical intertidal zones, remains poorly understood. This study examined the biometric characteristics and condition index of the cockle A. antiquata in relation to water quality parameters in the intertidal zone of Lhokseumawe, Indonesia, from August 2014 to March 2015. Monthly sampling of 50 cockles during low tide in the estuarine reservoir measured cockle weight, shell length, shell height, condition index, and water quality parameters, including temperature, pH, and salinity. Strong positive relationships were observed between shell length and cockle weight (R² = 0.847, r = 0.920), shell height and shell length (R² = 0.861, r = 0.927), and cockle weight and shell height (R² = 0.887, r = 0.941). Allometric models indicated negative allometry in these relationships. Analysis of the condition index revealed continuous dribble spawning throughout the study period. Water quality parameters included temperatures ranging from 28.2 - 32.2 °C (mean 30.02 ± 1.62 °C), salinity levels between 34.4 - 35.5 ppt (mean 35.08 ± 0.32 ppt), and pH values of 6.77 - 6.86 (mean 6.82 ± 0.03), reflecting favourable environmental conditions for cockle growth and reproduction.